Living Abroad, Facing Risks: How Prepared Are Indonesian Diaspora Students for Disasters? - Nugroho, Agung; Untarti, Reni; Irawan, Dedy; Mareza, Lia; Pria Wibowo, Anggun (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the level of preparedness among Indonesian diaspora students in the face of potential disasters, particularly earthquakes and tsunamis, and to identify aspects of preparedness that still need to be improved. Method: This study employed a quantitative approach using a survey method involving 30 fifth-grade students at Sekolah Indonesia Kuala Lumpur (SIKL), Malaysia. The instrument used was the LIPI-UNESCO/ISDR Disaster Preparedness Questionnaire Series 3, which covers four main parameters: knowledge and attitudes, emergency response plans, early warning systems, and resource mobilization. The data was analyzed by calculating the readiness index for each parameter and the overall student readiness index. Results: The research findings indicate that the disaster preparedness level of diaspora students falls into the "nearly ready" category, with an index score of 58.5. The knowledge and attitude (60.8) and emergency response plan (59.6) parameters showed relatively better results, indicating that the students already possess a basic understanding of disaster risks and initial response measures. However, the parameters for early warning systems (44.1) and resource mobilization (40) remain in the low category, indicating limitations in practical experience, understanding of early warning systems, and the ability to act quickly and in a coordinated manner when a disaster occurs. Novelty: This study offers a novel perspective by examining the disaster preparedness of Indonesian diaspora students in the context of cross-border education, where disaster risk characteristics vary. The study highlights how geographical displacement, limited experience with disasters, and differences in disaster communication systems influence students’ level of preparedness. In addition, this study integrates four dimensions of preparedness (knowledge and attitudes, emergency response planning, early warning systems, and resource mobilization) to provide a more comprehensive picture of the preparedness of diaspora students to cope with disasters.